Quantitative Analysis of Dihydroxybenzenes in Complex Water Samples Using Excitation-Emission Matrix Fluorescence Spectroscopy and Second-Order Calibration. (13th October 2014) - Chen, Hui; Lin, Zan; Tang, Hongmei; Wu, Tong; Tan, Chao
Abstract : The dihydroxybenzenes are organic intermediates in many fields for various purposes and have been widely recognized as fatal environmental pollutants. Simultaneous determination of these compounds is particularly important. These habitual methods are time-consuming and laborious. The combination of two-dimensional excitation-emission matrix (EEM) fluorescence and second-order calibration of parallel factor analysis (PARAFAC) was investigated for simultaneously determining catechol, hydroquinone, and tryptophan. A total of 25 samples were designed and are divided into a calibration set and a test set. An unexpected constituent was used as unknown interference. The EEM data were successfully decomposed into a four-factor model of PARAFAC. The resolved spectra excitation and emission profiles from PARAFAC algorithm were compared with the corresponding pure spectra to confirm the compounds in samples. Based on the decomposition, the final calibration models provided satisfactory concentration estimates. The mean recovery percentages were 98.3%, 101.7%, and 97.9% for catechol, hydroquinone, and tryptophan, respectively. The results reveal that the developed method is maybe a potential tool for simultaneous determination of phenolic components in water samples or other complex samples.